A Qualitative Study Of Anxiety And Coping Cycles In East Java Muaythai Athletes In The Sparring Category Using A Creative Viusal Approach - Rahayuni, Kurniati; Solehah, Alfiyatus (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
This research aims to be a reference for coaches, athletes, and Muaythai organization administrators in dealing with anxiety in athletes before competing, so they can perform optimally. This research uses qualitative methods with direct participation of researchers and is conducted at Koni East Java Province. Data were obtained from semi-structured interviews with 15 East Java Muaythai athletes in the fighting category who had competed at the provincial level. The results show three patterns of anxiety: (1) a pattern of progressive increase, where anxiety increases long before the day of the match and is difficult to reduce; (2) a pattern of performance decline, from high anxiety levels that do not decrease; and (3) a pattern of stagnation, where anxiety shows no significant change. This study produced three main patterns of anxiety analysis and it is hoped that future researchers can further develop the focus of the study.